Barbadoes. Countrywoman going to Market. - Forrest, A.S. (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This painting shows a lady going to the market with her goods loaded on her donkey’s back. This is a divided back postcard. Back of the postcard Letter is written : Darling Bill, I don’t think there are any donkeys at Bournemouth, not natives, only just one that I know of and that is there, or comes from Leicester. Tut Tut??. Have sent one for you on the other side. Am looking forward to having you both home again. I will write to Auntie Annie next week. Love to ??(undecipherable) all. From your Dad. Letter addressed to: Miss Bill Cartwright, 10 Camphell Road, Boscombe, Bournemouth CNTP W/F £6 (Handwritten in Pencil) Stamp marked: Leicester 8:30 pm MR 3 06 WIDE WIDE WORLD BARBADOES, Raphel Tuck & Sons’, “OILETTE” [Regd.] Postcard 7050 From “THE WEST INDIES,” illustrated by A. S. Forrest (A. & C. Black) Countrywoman going to Market. The soil of Barbados is very fertile, the climate also being agreeable (for the West Indies), and the rural population are enabled to earn a good living by disposing of their produce in the towns. Thither they trudge on every market day, carrying their burdens, conspicuous to all owing to their undisguised interest and curiosity in their novel surroundings. Note : Oilette is a term used by Tuck & Sons to refer to their postcard series that reproduced scenes from specially commissioned paintings rather than photographs.
Portrait; Color; 3 ½” x 5½ ”
Keywords: Street Vendors; Markets; Farmers’ Markets; Transportation; Mules; Donkeys; Women; Clothing and dress; Vendors; Hawkers